Disseminated peripheral neuroblastoma in a Rhodesian Ridgeback dog. Issue 4 (April 2017) - Cook, RW; Abraham, LA; McCowan, CI
Abstract : Case report: A 4‐year‐old neutered male Rhodesian Ridgeback dog with right‐sided Horner's syndrome, bilateral laryngeal paralysis, neck pain and bilateral hindlimb ataxia was euthanased following deterioration of its neurological status. Necropsy examination revealed an off‐white retropharyngeal neoplastic mass (100 × 30 × 30 mm) attached to the base of the skull on the right side and macroscopic nodular metastases in the spleen and three vertebral bodies (C6, C7 and T6), including a nodule attached to the dura at C7. Histological evidence of neuroblastic tumour was detected in these macroscopic lesions, a regional lymph node, bone marrow of a femur and all 15 vertebral bodies (C1–T8) examined, including the three with macroscopic metastases, and in the lumens of small blood vessels in the lungs and liver. Ganglion cell differentiation was detected only in the primary retropharyngeal mass, one splenic nodule and the C7 dural nodule. Neoplastic cells were immunoreactive to neurofilament protein (ganglion cells only), vimentin and synaptophysin, and were negative for S100 protein, GFAP, CD3 and Pax5. Conclusion: The diagnosis was disseminated peripheral neuroblastoma, differentiating subtype (International Neuroblastoma Pathology Classification), with likely primary involvement of the right cranial cervical ganglion. This appears to be the first report of neuroblastoma in a dog with widespread occult haematogenous metastasis to bone marrow.